ANALYSE PHYTOGÉOGRAPHIQUE DES PTÉRIDOPHYTES D’AFRIQUE CENTRALE: CAS DES ÉTAGES DES MONTAGNES DU PARC NATIONAL DE KAHUZI-BIEGA (RÉPUBLIQUE DÉMOCRATIQUE DU CONGO) - Jean De Dieu, Mangambu Mokoso; Elmar, Robbrecht; Honorine, Ntahobavuka Habimana; Van Diggelen, Ruurd (European Scientific Journal, ESJ, 2014)
This study comprises a phytogeographical analysis of forest ferns and their allies of the Kahuzi Biega National Park (KBNP), located in Democratic Republic of Congo (DRC). The phytogeographical and floristic affinities and dissimilarities were investigated for forested areas of the Albertine Rift, Continental Africa and some mountainous areas outside of Africa. This analysis was based on herbarium material collected in the mountains of KBNP (5987 specimens) and housed in various herbaria in Belgium, the Democratic Republic of Congo (DRC) and the Netherlands. The results showed that the majority of ferns in the mountains of the KBNP are also found in many other African areas (52.1% of the flora). Further, 41.9% of the species have a wide distribution outside of Africa, while endemic and sub-endemic species represent a mere 6% of the fern flora of KBNP. Within the related species, some showed a disjunction between the mountainous areas of Cameroon and the PNKB. The mountains of the Kivu- Ruwenzori area show greatest affinity between each other as well as other mountainous regions in western and southern Africa. The sub-montane zone of the PNKB is considered to be a transitional area between the Kahuzi mountain range and other regional centers of endemism.